PERSONALITY OF ANNA IN JODI PICOULT'S MY SISTER'S KEEPER:A PSYCHOANALYTIC APPROACH - ALWAFA, NIDA (2011)
The research is proposed to analyze personality of anna in a novel with the title My Sister's Keeper with Psychoanalytic Approach. There are two objectives: the first is to analyze the novel in term of structural elements, and the second is to analyze the novel based on Psychoanalytic Approach. This research is a descriptive qualitative research, using the novel of Jodi Picoult's My Sister's Keeper as the object of analysis. There are two kinds of data sources used in the analyzing, namely primary and secondary data sources. The primary data are the novel itself and the secondary data sources are some books, internet site and articles related to the subject. the technique of data collection in this research is library research by summaryzing, paraphrasing and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis. The outcome of the study reveals the relationship between the novel and the personality of major character. In My Sister's Keeper, Jodi Picoult describes how the personality of Anna to suing her parents for the right her body. In her novel My Sister's Keeper, Picoult describes how Anna denies to donate the kidney for her sister.